Perubahan Pemilikan Persekutuan Analisis Pembagian Laba dan Rugi dalam Pembubaran Persekutuan: Prinsip, Metode, dan Implikasi Akuntansi - Sri Lestari Yuli Prastyatini; Nur Anita Chandra Putry; Dini Desviani; Delon Ringu Langu; Keny Jerikho Kristian Kotto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The principle of profit and loss distribution upon dissolution of a partnership is based on the initial agreement of the partners, as stated in the partnership deed. If no agreement exists, then it is distributed based on the proportion of each partner's capital after recalculating existing assets and liabilities. This is done to ensure that the distribution of profits and losses remains fair and commensurate with the contributions and risks borne by each partner. Profit and loss distribution includes a fixed ratio method based on initial capital, salary distribution for managers who manage the business, distribution of interest on capital at an agreed rate, and bonuses to partners who incur greater losses. All of these methods aim to adjust for differences in non-financial contributions such as work or specialized expertise. The accounting process upon dissolution begins with the preparation of a liquidation balance sheet, which includes the sale of non-cash assets, priority payment of debts to creditors, closing the profit and loss account, and distributing profit and loss to partners in stages through capital balance adjustment entries. This requires careful recordkeeping to avoid a shortage of funds or undivided remaining assets.